(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Watiniasih NL, Budiarsa IN, Antara ING, Wiradana PA. 2022. Propolis extract as a green bacterial corrosion inhibitor on three types of metals. Biodiversitas 23: 4852-4860. Corrosion causes severe damage to various types of metals, which is a serious problem in the infrastructure sector. Several studies have been conducted to find more efficient natural inhibitors. This study was aimed to determine the effectiveness of antioxidants from propolis extract in inhibiting the growth of bacteria that cause corrosion on various metals. The ethanol extract was carried out to obtain the bioactive contained in the propolis extract, then analyzed its antioxidant activity with DPPH and characterized using GC-MS. Various concentration of propolis extract were tested on NA+1% Fe medium to determine its resistance to corrosion-causing bacteria. Propolis extract was tested on several types of metals in inhibiting the corrosion rate. The results showed that the tested propolis extract had strong antioxidant activity with an IC50 value of 82.496 ppm. The characterization of the metabolite profile showed that the propolis extract was dominated by chemical components that act as antioxidants and antibacterial agents. In the future, the results of this study can be used as a practical guide for the application of bioactive compounds through a biocontrol approach to the growth of corrosion-causing bacteria.